Traction and wear of an elastomer in combined rolling and sliding. (27th May 2015) - Rowe, Kyle G.; Bennett, Alexander I.; Sawyer, W. Gregory
Abstract: Under combined rolling and sliding materials can experience millions of cycles as well as complex loading and slip conditions, which can dramatically affect their friction and wear behaviour. It was shown that for a carbon black‐filled natural rubber compound in combined rolling and sliding contact with a smooth alumina coated disk, the traction coefficient, as a function of slip percent, was dependent upon the normal load and independent of rolling velocity. The wear rate of this material pair was found to be independent of slip percentage as well as rolling velocity but dependent upon sliding distance. The wear rate was found to be approximately the same for all tested cases (K ~ 1 × 10 −4  mm 3 ·Nm −1 ). The worn profiles of the ball specimens showed that this wear occurred preferentially on the left side (inner radius) of the contacting area. Copyright © 2015 John Wiley & Sons, Ltd.